Immunogenicity and safety of an investigational tetravalent recombinant subunit vaccine for dengue: results of a Phase I randomized clinical trial in flavivirus-naïve adults. Issue 9 (2nd September 2019) - Manoff, Susan B.; Sausser, Michele; Falk Russell, Amy; Martin, Jason; Radley, David; Hyatt, Donna; Roberts, Christine C.; Lickliter, Jason; Krishnarajah, Janakan; Bett, Andrew; Dubey, Sheri; Finn, Tyler; et al.
ABSTRACT: There is an unmet medical need for vaccines to prevent dengue. V180 is an investigational recombinant subunit vaccine that consists of truncated dengue envelope proteins (DEN-80E) for all 4 serotypes. Three dosage levels of the tetravalent DEN-80E antigens were assessed in a randomized, placebo-controlled, Phase I dose-escalation, first-in-human proof-of-principle trial in healthy, flavivirus-naïve adults in Australia (NCT01477580). The 9 V180 formulations that were assessed included either ISCOMATRIX™ adjuvant (2 dosage levels), aluminum-hydroxide adjuvant, or were unadjuvanted, and were compared to phosphate-buffered saline placebo. Volunteers received 3 injections of assigned product on a 0, 1, 2 month schedule, and were followed for safety through 1 year after the last injection. Antibody levels were assessed at 6 time-points: enrollment, 28 days after each injection, and 6 and 12 months Postdose 3 (PD3). Of the 98 randomized participants, 90 (92%) received all 3 injections; 83 (85%) completed 1-year follow-up. Immunogenicity was measured by a qualified Focus Reduction Neutralization Test with a 50% neutralization cutoff (FRNT50 ). All 6 V180 formulations with ISCOMATRIX™ adjuvant showed robust immunogenicity, while the 1 aluminum-adjuvanted and 2 unadjuvanted formulations were poorly immunogenic. Geometric mean antibody titers generally declined at 6 months and 1 year PD3. All 9 V180 formulations were generally well tolerated. Formulations with ISCOMATRIX™ adjuvant were associated with more adverse events than aluminum-adjuvanted or unadjuvanted formulations.